Language and gender - Fagard, Benjamin; Gil, Cristina; Faria, Rita; Meister Ko. Freitag, Raquel; Chenoll, Antonio; Navas, Grauben; Diewald, Gabriele; Elmiger, Daniel; Meulleman, Machteld; Abrantes, Ana Margarida; Schütze, Christin; Steriopolo, Olga; et al. (UCP Press, 2026)
This book explores the linguistic representation of gender and how gender asymmetries in language structure both mirror and further drive the imbalance of power and visibility of gender groups in society. These inequalities may also impact the way we conceptualize gender, potentially contributing to the perpetuation of gender disparities. By examining the intricate relations between language, gender, and society, this book aims to shed light on some of the many ways language shapes perceptions, relations, and social structures.